Currículo e formação de professores: um estudo e proposta curricular do curso de pedagogia da Universidade Estadual de Goiás - LIMONTA, Sandra Valéria (2009)
This study is related to the Teacher‟s Formation and Professionalisation research guideline. The work theme can be generally defined as teacher‟s formation, however, the specific object is the curriculum proposal for teaching training of the pedagogics course on Goiás State University. The principal objective of this research is to analyses the limits and possibilities of curriculum´s pedagogics course of this education institution and its relations with the educational policies for teacher training in higher education in Brazil. The research part of the understanding of the curriculum as a cultural and social construction, and also a conflicting field of debate, in which different perspectives of training will affect. Such epistemological perspectives are a landmark and a guideline policy that can be perceived when considering the curriculum components and when it discusses the curriculum in action. The guiding questions of the thesis are: What are the limits and possibilities of the unified curriculum of the teacher‟s training course and how this curriculum is articulated to the educational policies for teacher training? As was the UEG and the course of education in the context of Brazilian higher education? Who are the teachers and students of the pedagogics course? How teachers and students have understood and realized the proposed structure of the unified curriculum? With the search method of the historical and dialectical materialism, from a context of higher education and the teaching formation course on pedagogics in Brazil, the university is presented as the place of production and criticism of culture and knowledge and as a privileged and essential training of teachers place. and analyze the policies of teacher education and the National Curricular Guidelines for the Course of Pedagogy in Brazil. In this scenario, is presented the UEG as social and political institution, highlighting the contradictions between the role of universities in offering higher education in the state, particularly in inland regions, and its characteristic of government program, that generated an accelerated process of expansion and diversification and also various problems. From empirical evidence and taking the teaching as the primary category of analysis, presenting the social and professional profile of teachers and students of the pedagogics course, is described and analyzed how they evaluate the curriculum in action. The analyze of the empirical data resulted in the construction of a thesis on planning and curriculum development in the pedagogics course of teaching formation, presented as a reflection on the integrated curriculum, the teaching and research in a historical-critical as formative principles and priorities guiding to the planning and development curriculum of this course